Strategies for developing evidence-based practice skills across the nursing curriculum - Vásquez, Skarlet Marcell; Bonilla-Marciales, Adriana Patricia; Jaimes-Valencia, Mary Luz (Revista Cuidarte, 2023)
Introduction: Teaching evidence-based practice is a recognized worldwide strategy for improving health care quality. Objective: To identify the level of evidence-based practice competencies of nursing students according to the characteristics of the curriculum followed in a Colombian university. Materials and Methods: Cross-sectional study measuring nursing students in three periods (N=125): Curriculum-1 without research training (n=24); Curriculum-2 with research training (n=55); Curriculum-3 with evidence-based practice training (n=46). The primary outcome was evidence-based practice competencies measured by attitude, knowledge, and skills. Results: The global competence score was 4.08 (interquartile range = 3.84–4.32), and no statistically significant differences were observed between the scores obtained by students in the three curricula. However, knowledge competencies for evidence-based practice were significantly higher in the Curriculum 3 group. Discussion: Some authors have described the relationship between the timing of curricular transformations and the development of progressive competencies as a staggered process whose results are reflected in at least one complete curricular cycle after its implementation. Conclusions: The curricular adjustments made at this institution have improved the perception of knowledge in evidence-based practice among nursing students; however, it is necessary to continue working on effective pedagogical strategies that enhance the skills for its implementation. This information provides guidance for curriculum planning. How to cite this article: Vásquez Skarlet Marcell, Bonilla-Marciales Adriana Patricia, Jaimes-Valencia Mary Luz. Estrategias para el desarrollo de habilidades en práctica basada en la evidencia a través del currículo de enfermería. Revista Cuidarte. 2023;14(3):e3089. http://dx.doi.org/10.15649/cuidarte.3089